2018
DOI: 10.1371/journal.pone.0194320
|View full text |Cite
|
Sign up to set email alerts
|

Disorder strength measured by quantitative phase imaging as intrinsic cancer marker in fixed tissue biopsies

Abstract: Tissue refractive index provides important information about morphology at the nanoscale. Since the malignant transformation involves both intra- and inter-cellular changes in the refractive index map, the tissue disorder measurement can be used to extract important diagnosis information. Quantitative phase imaging (QPI) provides a practical means of extracting this information as it maps the optical path-length difference (OPD) across a tissue sample with sub-wavelength sensitivity. In this work, we employ QP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…Here, we use our recently devised color spatial light interference microscopy (cSLIM) 23 as a quantitative phase imaging (QPI) technique [24][25][26][27][28][29][30][31][32][33][34] to quantify myelin in brain tissue. QPI is a technique that can evaluate nanometer scale pathlength changes in biological specimens.…”
mentioning
confidence: 99%
“…Here, we use our recently devised color spatial light interference microscopy (cSLIM) 23 as a quantitative phase imaging (QPI) technique [24][25][26][27][28][29][30][31][32][33][34] to quantify myelin in brain tissue. QPI is a technique that can evaluate nanometer scale pathlength changes in biological specimens.…”
mentioning
confidence: 99%
“…4 Quantitative phase imaging (QPI) 5 is a label-free microscopy technique where contrast is generated by the optical path-length difference (OPD), which is the product of the local thickness and refractive index of the specimen. [5][6][7] For a thin specimen, such as a tissue histology, the thickness can be considered spatially invariant, in which case QPI images are proportional to a mean refractive index map, 8,9 i.e., a refractive index map integrated along the z axis. Since the refractive index is proportional to the dry mass content of cells and cellular matrix, it informs on tissue density as well as cell organization within tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Our group also showed that the disorder strength measured by spatial light interference microscopy (SLIM), a sensitive white light QPI method, is a quantitative marker of malignancy that can be used to classify benign and malignant breast tissue microarray (TMA) cores. 8 In this paper, we propose the local spatial autocorrelation length as an intrinsic marker of nanoscale morphological alteration in fixed tissue biopsies. Since the spatial autocorrelation length is related to the spatial refractive index fluctuations, which has been shown to detect malignancy in previous works, the length in a local region of tissue can be correlated with carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Quantitative phase imaging (QPI) 5 is a label-free microscopy technique where contrast is generated by the optical path-length difference (OPD), which is the product of the local thickness and refractive index of the specimen. [5][6][7] For thin specimen, such as a tissue histology, the thickness can be considered spatially invariant, in which case QPI images are proportional to a mean refractive index map, 8,9 i.e., refractive index map integrated along z-axis. Since the refractive index is proportional to the dry mass content of cells and cellular matrix, it informs on tissue density as well as cell organization within tissue.…”
Section: Introductionmentioning
confidence: 99%
“…38 Our group also showed that the disorder strength measured by spatial light interference microscopy (SLIM), a sensitive white light QPI method, is a quantitative marker of malignancy that can be used to classify benign and malignant breast tissue microarray (TMA) cores. 8 In this paper, we propose the local spatial autocorrelation length as a new intrinsic marker of nanoscale morphological alteration in fixed tissue biopsies. Since the spatial autocorrelation length is related to the spatial refractive index fluctuations, which has been shown to detect malignancy in previous works, the length in a local region of tissue can be correlated with carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%